2021
DOI: 10.1021/acsami.0c19117
|View full text |Cite
|
Sign up to set email alerts
|

Coaxial Ni–S@N-Doped Carbon Nanofibers Derived Hierarchical Electrodes for Efficient H2 Production via Urea Electrolysis

Abstract: Electrochemical water splitting into hydrogen is a promising strategy for hydrogen production powered by solar energy. However, the cell voltage of an electrolyzer is still too high for practical application, which is mainly limited by the sluggish oxygen evolution reaction process. To this end, hybrid water electrolyzers have drawn tremendous attention. Herein, coaxial Ni/Ni 3 S 2 @N-doped nanofibers are directly grown on nickel foam (NF), which is highly active for hydrogen evolution reaction. Meanwhile, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 71 publications
0
35
0
Order By: Relevance
“…In addition, we found that the electrocatalytic urea oxidation rate gradually increased as the temperature of the electrolyte increased, which was related to the rate constant of the chemical reaction. [ 34 ] By transforming the Arrhenius formula, we can see that the Ni 0.8 Co 0.2 DHs had a lower apparent E a value of 12.45 kJ mol −1 , while the values of Ni 0.67 Co 0.33 DHs, Ni 0.5 Co 0.5 DHs, and Ni 0.2 Co 0.8 DHs were 13.88, 23.91, and 37.50 kJ mol −1 , respectively (Figure S5, Supporting Information). This result indicates that Ni 0.8 Co 0.2 DHs possessed a lower apparent barrier for the CN bond cleavage in urea.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we found that the electrocatalytic urea oxidation rate gradually increased as the temperature of the electrolyte increased, which was related to the rate constant of the chemical reaction. [ 34 ] By transforming the Arrhenius formula, we can see that the Ni 0.8 Co 0.2 DHs had a lower apparent E a value of 12.45 kJ mol −1 , while the values of Ni 0.67 Co 0.33 DHs, Ni 0.5 Co 0.5 DHs, and Ni 0.2 Co 0.8 DHs were 13.88, 23.91, and 37.50 kJ mol −1 , respectively (Figure S5, Supporting Information). This result indicates that Ni 0.8 Co 0.2 DHs possessed a lower apparent barrier for the CN bond cleavage in urea.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we found that the electrocatalytic urea oxidation rate gradually increased as the temperature of the electrolyte increased, which was related to the rate constant of the chemical reaction. [34] By transforming the Arrhenius formula, we can see that the…”
Section: Electrocatalytic Performance Of Nico Dhs Catalystsmentioning
confidence: 99%
“…Here, future perspectives are discussed: Developing highly efficient UOR catalysts, in terms of boosted catalytic current, low overpotential and durable catalytic performance, is highly desirable. The majority of the prepared catalysts are nickel oxides and hydroxides at early stages, while nickel sulfides [ 115 , 116 , 117 , 118 ], selenides [ 62 , 63 ], phosphides [ 119 , 120 ] and nitrides [ 111 ] have shown appreciable UOR performance in recent years. In addition, Ni-based Prussian blue analogues [ 17 ] and perovskites [ 121 ] have also been revealed as promising candidates for the UOR.…”
Section: Discussionmentioning
confidence: 99%
“…The lower apparent barrier of the C-N bond cleavage in urea for a/b-NiMoO 4 @NF indicates its easy oxidation into CO 2 and N 2 . 48 According to the previous studies, 13,49 the rate-determining step for the UOR is CO 2 desorption; hence, the CO 2 temperature-programmed desorption (CO 2 -TPD) measurements are conducted on both the a/b-NiMoO 4 @NF and a-NiMoO 4 @NF electrodes. It is observed from Fig.…”
Section: Electrochemical Performancementioning
confidence: 99%